Հուշկապարիկի գաղափարը հայ միջնադարյան հավատալիքներում - Հ. Վ. Հայրապետյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Символ «h'ушкапарик» своим глубинным смыслом связан с наиболее ранними мифологическими представлениями армянского народа. В эпоху язычества этот символ имел отношение к культу богини Анаhит. The symbol „HUSHKAPARIK" in its deep meaning is associated with the earliest mythological beliefs of the Armenians. At the period of paganism this symbol was associated with the cult of goddess Anahit.
Keywords: History; Geography; Anthropology; Recreation; Medieval History; Folklore; D History